Sistem Informasi Manajemen Sumber Daya Manusia Pada Universitas Muhammadiyah Jambi - Rafiezah Rizcha, Yasstyh; Yaakub, Saleh (LPPM Universitas Dinamika Bangsa, 2023)
Management of human resources is something that needs to be considered in a university, because the management of human resources is included in the management of higher education. Information systems are really needed in managing at a Muhammadiyah University, information systems must also be in accordance with existing management at Muhammadiyah University and in management there are general principles that include planning, organizing, mobilizing and ensuring. using modeling UML (Unified Modeling Language) with the following steps: Determining Initial Planning, Analyzing Information Systems Currently Used, Modeling Information Systems Using UML Modeling (Unified Modeling Language). At this stage, create a model of information system requirements with Use Cases, Activity Diagrams and Class Diagrams and Build Information System Prototypes. The results of this information system design are to assist HR management in collecting employee data and also to facilitate the process of applicants becoming employees at the University of Muhammadiyah Jambi. With this information system, it is also easy to find information about employee recruitment and employee development. This research resulted in a design made using object-oriented methods with UML, which resulted in a prototype of an HR management information system, especially employee recruitment at the University of Muhammadiyah Jambi